2018
DOI: 10.1161/hypertensionaha.117.10390
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for the Immunoproteasome Subunit PSMB10 in Angiotensin II–Induced Atrial Fibrillation in Mice

Abstract: Angiotensin II (Ang II) and inflammation are associated with pathogenesis of atrial fibrillation (AF), but the underlying molecular mechanisms of these events remain unknown. The immunoproteasome has emerged as a critical regulator of inflammatory responses. Here, we investigated its role in Ang II-induced AF in immunosubunit PSMB10 (also known as β2i or LMP10) knockout (KO) mice. AF was induced by Ang II infusion (2000 ng/min per kg). PSMB10 expression and trypsin-like activity were increased in atrial tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 39 publications
4
99
0
Order By: Relevance
“…The immunoproteasome has critical functions in the regulation of protein degradation, immune cell homeostasis, oxidative stress and cell apoptosis [13,14]. Recently, we showed that the β2i and β5i subunits are involved in the development of cardiac remodeling, atrial fibrillation and retinopathy, thus extending previous knowledge about the immunoproteasome [15][16][17][18]. Notably, subunit β5i was upregulated in the shoulder areas of symptomatic carotid plaques as compared with non-symptomatic plaques, suggesting a correlation between β5i activity and plaque instability [19].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The immunoproteasome has critical functions in the regulation of protein degradation, immune cell homeostasis, oxidative stress and cell apoptosis [13,14]. Recently, we showed that the β2i and β5i subunits are involved in the development of cardiac remodeling, atrial fibrillation and retinopathy, thus extending previous knowledge about the immunoproteasome [15][16][17][18]. Notably, subunit β5i was upregulated in the shoulder areas of symptomatic carotid plaques as compared with non-symptomatic plaques, suggesting a correlation between β5i activity and plaque instability [19].…”
Section: Introductionsupporting
confidence: 56%
“…It is well known that immune and inflammatory cells, including macrophages, T cells and dendritic cells, play an important role in the development and progression of atherosclerosis [23,24]. The immunoproteasome is expressed constitutively in immune cells, and can be induced in immune and non-immune cells upon exposure to pro-inflammatory stimuli such as viruses, angiotensin II and high salt, thus contributes to the regulation of immuno-inflammatory diseases, including viral myocarditis, hypertrophic remodeling, atrial fibrillation and vascular cell apoptosis [15,16,18,[25][26][27][28]. Here, the results presented showed that β5i was upregulated in the atherosclerotic plaques of eKO mice (Figure 1); genetic ablation or inhibition of β5i reduced lesional accumulation of apoptotic cells but enhanced MERTK-mediated efferocytosis, therefore inhibited necrotic core formation and atherosclerosis progression (Figures 2-4).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of Ang II infusion, intracardiac pacing was performed in mice through the insertion of an eight-electrode catheter (1.1F, octapolar EP catheter, Scisense, London, Ontario, Canada) via the jugular vein and its advancement into the right atrium and ventricle [20]. The inducibility of AF was measured by applying a 5-s burst using an automated stimulator as described previously and recorded with a computer-based data acquisition system (GY6328B; Henan Huanan Medical Science and Technology, Co., Ltd., Zhengzhou, HA, CHN) [4,20]. A series of bursts were repeated three times after stabilization for 5 min.…”
Section: Arrhythmia Inducibility and Durationmentioning
confidence: 99%
“…Since atrial structural remodeling is a major risk factor for AF [4], we then examined the effect of LDN on atrial dilation in vivo. Echocardiography revealed that the Ang IIinduced dilation of the left atrium (LA) observed in vehicletreated WT mice was also attenuated in LDN-treated mice (Fig.…”
Section: Administration Of Ldn Inhibits Ang Ii-induced Systolic Bloodmentioning
confidence: 99%
See 1 more Smart Citation